Scaffolded Small Group Discussion and Picture Series in Enhancing EFL Learners' Writing Performance - Nabila, Nada; Munifatullah, Feni; Kadaryanto, Budi (Universitas PGRI Sumatera Barat, 2025)
Writing proficiency is a crucial skill in language learning, yet many students struggled with structuring their ideas coherently. While various strategies had been explored to enhance writing skills, limited research had examined the integration of collaborative learning and visual aids, such as picture series, in small group discussions. This study investigated the effectiveness of scaffolded small group discussions and picture series in improving students' writing performance compared to the original small group discussion. Employing a quasi-experimental design, the study involved two groups of eleventh-grade students at SMAN 9 Bandar Lampung, with a pre-test and post-test administered to measure improvements. The quantitative data, analyzed using an Independent-Sample t-test in SPSS, revealed a significant improvement in students’ writing performance, particularly in rhetorical structure. The findings suggested that integrating scaffolded small group discussions with picture series provided a structured and collaborative learning environment that enhanced students' ability to organize their ideas coherently. This study contributed to the growing body of research on effective writing instruction and underscored the importance of collaborative and visual learning techniques in improving writing skills.